Insulin‐like growth factor 1 deficiency exacerbates hypertension‐induced cerebral microhemorrhages in mice, mimicking the aging phenotype. Issue 3 (14th March 2017) - Tarantini, Stefano; Valcarcel‐Ares, Noa M.; Yabluchanskiy, Andriy; Springo, Zsolt; Fulop, Gabor A.; Ashpole, Nicole; Gautam, Tripti; Giles, Cory B.; Wren, Jonathan D.; Sonntag, William E.; Csiszar, Anna; Ungvari, Zoltan
Summary: Clinical and experimental studies show that aging exacerbates hypertension‐induced cerebral microhemorrhages (CMHs), which progressively impair neuronal function. There is growing evidence that aging promotes insulin‐like growth factor 1 (IGF‐1) deficiency, which compromises multiple aspects of cerebromicrovascular and brain health. To determine the role of IGF‐1 deficiency in the pathogenesis of CMHs, we induced hypertension in mice with liver‐specific knockdown of IGF‐1 ( Igf1 f/f + TBG‐Cre‐AAV8) and control mice by angiotensin II plusl ‐NAME treatment. In IGF‐1‐deficient mice, the same level of hypertension led to significantly earlier onset and increased incidence and neurological consequences of CMHs, as compared to control mice, as shown by neurological examination, gait analysis, and histological assessment of CMHs in serial brain sections. Previous studies showed that in aging, increased oxidative stress‐mediated matrix metalloprotease (MMP) activation importantly contributes to the pathogenesis of CMHs. Thus, it is significant that hypertension‐induced cerebrovascular oxidative stress and MMP activation were increased in IGF‐1‐deficient mice. We found that IGF‐1 deficiency impaired hypertension‐induced adaptive media hypertrophy and extracellular matrix remodeling, which together with the increased MMP activation likely also contributes to increased fragility of intracerebral arterioles. Collectively, IGF‐1 deficiency promotes the pathogenesis of CMHs, mimicking the aging phenotype, which likely contribute to its deleterious effect on cognitive function. Therapeutic strategies that upregulate IGF‐1 signaling in the cerebral vessels and/or reduce microvascular oxidative stress, and MMP activation may be useful for the prevention of CMHs, protecting cognitive function in high‐risk elderly patients.